The analysis of ecological plasticity and stability of the spring barley varieties in the station testing - E. G. Filippov; A. A. Dontsova; R. N. Bragin (Зерновое хозяйство России, 2019)
Currently spring barley breeding is aimed at breeding of adaptive varieties capable to produce stable yields even in the conditions of increasing climate aridity. To study this issue, there has been carried out an estimation of environmental plasticity and stability of spring barley varieties in the southern part of the Rostov region. The study was conducted in the FSBSI “Agricultural Research Center “Donskoy” in 2016-2018. There were studied 10 spring barley varieties of various geographical origin, including the 6 Russian, 2 Ukrainian and 2 German, sown in three replications. The area of the plot was 10 m2, the variety “Ratnik” was given as a standard variety. There was used the method of S. A. Eberchart, W. A. Rassel (1966), amended by V. A. Zykina (2005). According to the results, there were identified such responsive varieties as “Priazovsky 9”, “Gris”, “Grays” and such stable varieties as “Ratnik”, “Shchedry”, “Novik”, “Vakula”, “Odessky 22”. The varieties “Gris”, “Grays” and “Thessa” showed the best results among the studied varieties. Their regression lines exceeded the line of average productivity and formed the largest average productivity in respect to other varieties. The “year” factor had the greatest effect on the yield (94.9%). The obtained data can be explained by the environmental conditions that significantly influenced on spring barley productivity over the years of research (2016-2018).